Comparing Physician and Nurse Eastern Cooperative Oncology Group Performance Status (ECOG‐PS) Ratings as Predictors of Clinical Outcomes in Patients with Cancer. (21st June 2019) - Neeman, Elad; Gresham, Gillian; Ovasapians, Navasard; Hendifar, Andrew; Tuli, Richard; Figlin, Robert; Shinde, Arvind
Abstract: Background: The Eastern Cooperative Oncology Group Performance Status (ECOG‐PS) scale is commonly used by physicians and nurses in oncology, as it correlates with cancer morbidity, mortality, and complications from chemotherapy and can help direct clinical decisions and prognostication. This retrospective cohort study aimed to identify whether ECOG‐PS scores rated by oncologist versus nurses differ in their ability to predict clinical outcomes. Materials and Methods: Over 19 months, 32 oncologists and 41 chemotherapy nurses from a single academic comprehensive cancer center independently scored ECOG‐PS (range: 0–5) for a random sample of 311 patients with cancer receiving chemotherapy. Logistic regression models were fit to evaluate the ability of nurse and physician ECOG‐PS scores, as well as the nurse‐physician ECOG‐PS score difference (nurse minus physician), to predict the occurrence of chemotherapy toxicity (CTCAE v4, grade ≥3) and hospitalizations within 1 month from ECOG‐PS ratings, as well as 6‐month mortality or hospice referrals. Results: Physician/nurse ECOG‐PS agreement was 71% (Cohen's κ = 0.486, p < .0001). Nurse ECOG‐PS scores had stronger odds ratio for 6‐month mortality or hospice (odds ratio [OR], 3.29, p < .0001) than physician ECOG‐PS scores (OR, 2.71, p = .001). Furthermore, ECOG‐PS ratings by nurses, but not physicians, correlated with 1‐month chemotherapy toxicity (OR, 1.44, p = .021) and 1‐month hospitalizations (OR, 1.57, p = .041). Nurse‐physician disagreement, but only when physicians gave "healthier" (lower) ratings, was also associated with worse outcomes (chemotherapy toxicity OR = 1.51, p = .045; 1‐month hospitalization OR, 1.86, p = .037; 6‐month mortality or hospice OR, 2.99, p < .0001). Conclusion: Nurse ECOG‐PS ratings seem more predictive of important outcomes than those of physicians, and physician‐nurse disagreement in ECOG‐PS ratings predicts worse outcomes; scoring by nurses may result in additional clinical benefit. Implications for Practice: Nurse‐rated Eastern Cooperative Oncology Group Performance Status (ECOG‐PS) scores, compared with those rated by oncologists, better predicted hospitalizations and severe chemotherapy toxicity within 1 month from ECOG‐PS assessment, as well as mortality or hospice referrals within 6 months. Physician‐nurse disagreement in ECOG‐PS scoring was associated with worse hospitalization, chemotherapy toxicity, and mortality and hospice referral rates. Rating performance statuses of patients with cancer by nurses instead or in addition to oncologists can result in additional clinical benefits, such as improved prognostication, as well as better informed clinical decision making regarding whether or not to administer chemotherapy, the need for additional supportive care, and goals of care discussions. Abstract : This article reports on differences in ECOG performance scores assessed by oncologists versus nurses, focusing on whether the ratings differed in accurate prediction of clinical outcomes.